GAMBARAN EFEKTIFITAS PETIDIN 25 MG INTRAVENA UNTUK MENGURANGI REAKSI MENGGIGIL PADA PASIEN SEKSIO SESAREA PASCA ANESTESI SPINAL DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Masyitah, Sri Utari; ", Sony; Anggraini, Dewi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Shivering is a common complication in patient who received general dan regional anesthesia. In caesarean section, anesthesia technique that usually used is spinal anesthesia. The Incidence of post spinal anesthesia shivering in caesarean section was 85%. This condition wasn't comfortable for patient and would affect the ECG, blood pressure and oxygen saturation. Increasing of oxygen saturation on shivering would make hypoxemia for both mother and fetus. This research is a descriptive prospective study with consecutive sampling methods to discover the effectiveness of pethidine 25 mg intravenouse to reduce post spinal anesthesia shivering in caesarean section in general hospital of Riau province. This study used 30 patients of caesarean section who had post spinal anesteshia shivering in operation room in general hospital of Riau province. The results of this research were petidhine 25 mg intravenous is effective in amongst 30 samples, 16 shivering has decrease in pethidine 10 mg and 14 patient with 25 mg pethidine intravenous. After the surgery, 2 samples had recurrent shivering. The Onset of pethidine amongst 30 patients were ceased in 5 minutes in 28 patients and 10 minutes in 2 patients.Keywords: shivering, effectiveness pethidine, caesarean section, spinal anesthesia